Organizational Risk Factors for Job Stress. 1995
DOI: 10.1037/10173-002
|View full text |Cite
|
Sign up to set email alerts
|

Perception of support from the organization in relation to work stress, satisfaction, and commitment.

Abstract: In this chapter, we examine, as others have, the relationships between such concepts as work stress, social support, job satisfaction, and organizational commitment. Our aim is t o show that employees' "global belief concerning the organization's commitment to them" (Eisenberger, Fasolo, & Davis-Lamastro, 1990, p. 57) is a central factor in moderating the effects of work stress on them and on the organization (cf. Eisenberger et al., 1990;Eisenberger, Huntington, Hutchinson, & Sowa, 1986). First, we provide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 35 publications
3
48
0
2
Order By: Relevance
“…Organizational policies and practices are two of the important elements that form the basis of the employee's assessment of organizational support (Guzzo, Noonan, & Elron, 1994). Research evidence has also shown that POS reduces work stress and acts as a buffer to work stress (Babakus, Cravens, Johnson, & Moncrief, 1996;Guzzo et al, 1994;Jones, Flynn, & Kelloway, 1995;Stamper & Johlke, 2003). We argue that the moderating effect of POS will operate in two fundamental ways.…”
Section: Perceived Organizational Support (Pos)mentioning
confidence: 87%
“…Organizational policies and practices are two of the important elements that form the basis of the employee's assessment of organizational support (Guzzo, Noonan, & Elron, 1994). Research evidence has also shown that POS reduces work stress and acts as a buffer to work stress (Babakus, Cravens, Johnson, & Moncrief, 1996;Guzzo et al, 1994;Jones, Flynn, & Kelloway, 1995;Stamper & Johlke, 2003). We argue that the moderating effect of POS will operate in two fundamental ways.…”
Section: Perceived Organizational Support (Pos)mentioning
confidence: 87%
“…Thus, we explore a direct relationship between perceived organizational support for health and safety citizenship behaviors (H2a). Furthermore, because employees who perceive an organization to care for their health also tend to show enhanced work performance (Jones et al, 1995;Wilson et al, 2004;Browne, 2000), it is expected that perceived organizational support for health is also associated with OCBs (H2b), which has not been examined within the literature. We hypothesize:…”
Section: Insert Figure 1 Herementioning
confidence: 99%
“…POS has been found to be influenced by policies, procedures, and decisions indicative of the organization's concern with employee welfare and the organization's favorable evaluation of employee contributions. POS was positively related to perceived sufficiency of pay and to perceived sufficiency of family-oriented policies and actions (Guzzo, Noonan, & Elron, 1994), high-quality employee-supervisor relationships, favorable developmental training experiences and promotions (Wayne et al, 1997), clearly stated guidelines defining appropriate work behavior and job demands (Hutchison, 1997;B. Jones, Flynn, & Kelloway, 1995), participation in goal setting, receipt of performance feedback (Hutchison, 1997;Hutchison & Garstka, 1996), supportive communications with immediate supervisors and upper management (Allen, 1992(Allen, , 1995, and procedural justice in performance-appraisal decisions (Fasolo, 1995;Moorman, Blakely, & Niehoff, 1998).…”
Section: Reciprocation Wariness and Perceivedmentioning
confidence: 99%